2003
DOI: 10.1038/sj.bjc.6601170
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of breast cancer genetics services in South East Scotland: psychological impact

Abstract: This study compared the psychological impact of two models of breast cancer genetics services in South East Scotland. One hundred and seventy general practices were randomised to refer patients to the existing standard regional service or the novel communitybased service. Participants completed postal questionnaires at baseline (n ¼ 373), 4 weeks (n ¼ 276) and 6 months (n ¼ 263) to assess perceived risk of breast cancer, subjective and objective understanding of genetics and screening issues, general psycholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
56
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 18 publications
6
56
0
Order By: Relevance
“…In the trial by Brain et al (2000), the addition of specialist genetic assessment to the standard surgical consultation had no effect on patients' psychological outcomes, risk perception or satisfaction, although knowledge of cancer genetics showed greater improvement. The other RCT found community-based genetic nurse specialists to be generally comparable to the standard service (consultant geneticist), in terms of psychosocial outcomes and patient satisfaction, with the additional benefit of lower staff and patient costs (Fry et al, 2003;Holloway et al, 2004).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In the trial by Brain et al (2000), the addition of specialist genetic assessment to the standard surgical consultation had no effect on patients' psychological outcomes, risk perception or satisfaction, although knowledge of cancer genetics showed greater improvement. The other RCT found community-based genetic nurse specialists to be generally comparable to the standard service (consultant geneticist), in terms of psychosocial outcomes and patient satisfaction, with the additional benefit of lower staff and patient costs (Fry et al, 2003;Holloway et al, 2004).…”
Section: Discussionmentioning
confidence: 97%
“…Alternative models for how nurse counsellors might provide a risk assessment service include the concept of working in liaison or outreach settings (Emery et al, 1999;Fry et al, 1999). Two randomised controlled trials have reported on different models of service delivery for genetic counselling for risk of breast cancer (Brain et al, 2000;Fry et al, 2003). In the trial by Brain et al (2000), the addition of specialist genetic assessment to the standard surgical consultation had no effect on patients' psychological outcomes, risk perception or satisfaction, although knowledge of cancer genetics showed greater improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the trial procedures have been described in detail Fry et al, 2003), but briefly the trial groups were: Standard (regional) service Women were sent a family history form to complete. The family history form requested information about first-, second-and third-degree relatives.…”
Section: Methodsmentioning
confidence: 99%
“…A model of cancer genetic services has been proposed (Campbell et al, 1995Fry et al, 2003), whereby genetic nurse specialists could offer clinics within GP locality areas to carry out risk assessment, provide counselling for those whose risk was not significantly increased and mediate referral of those at higher risk to the specialist service. It was hoped that this would provide improved support to primary care and better services for those not at increased risk, while encouraging more cost-effective use of specialist resources for those at increased risk of developing breast cancer.…”
mentioning
confidence: 99%